2021
DOI: 10.1186/s12885-021-08559-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel ferroptosis-related 12-gene signature predicts clinical prognosis and reveals immune relevancy in clear cell renal cell carcinoma

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is still highly aggressive and lethal even with various therapeutic approaches. As the kidney is an iron metabolism-related organ, exploring and assessing the clinical value of ferroptosis, an iron-dependent regulated cell death, is practical and important. Methods Prognostic ferroptosis-related differentially expressed genes (DEGs) were identified from the KIRC cohort in the cancer genome atlas (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 69 publications
4
49
0
Order By: Relevance
“…In addition, ICGC cohorts were used to evaluate the constructed model, which showed a good ability to predict the survival rate of patients with ccRCC (Supplementary Figure 2A-E). These results showed that the FRlncRNA signature can be a good indicator in predicting the prognosis of patients compared with other existing signatures reported in recent studies (Supplementary Table S2) (Canxuan and Dan, 2021;Hong et al, 2021;Ma et al, 2021;Xing et al, 2021;Yu et al, 2021;Zheng et al, 2021). Taken together, our data implied that the FRlncRNA signature showed a stable prognostic-predictive ability.…”
Section: Validation Of the Frlncrna Signaturesupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, ICGC cohorts were used to evaluate the constructed model, which showed a good ability to predict the survival rate of patients with ccRCC (Supplementary Figure 2A-E). These results showed that the FRlncRNA signature can be a good indicator in predicting the prognosis of patients compared with other existing signatures reported in recent studies (Supplementary Table S2) (Canxuan and Dan, 2021;Hong et al, 2021;Ma et al, 2021;Xing et al, 2021;Yu et al, 2021;Zheng et al, 2021). Taken together, our data implied that the FRlncRNA signature showed a stable prognostic-predictive ability.…”
Section: Validation Of the Frlncrna Signaturesupporting
confidence: 75%
“…Through linear correlation analysis (R > 0.3 and p < 0.001) and literature retrieval ( Shao et al, 2019 ; Xiong et al, 2021a ; Hong et al, 2021 ), we selected three target genes (BNIP3, RRM2, and GOT1) for further verification. BNIP3 ( p < 0.05) and RRM2 ( p < 0.05) were significantly upregulated in ccRCC tissues, but GOT1 ( p < 0.05) was significantly downregulated in ccRCC tissues ( Figures 11A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, FANCD2 plays an immunosuppressive role by downregulating immunostimulators, such asIL6R, TMEM173, TNFSF13, CD40LG, and HHLA2. Therefore, the results implied that FANCD2 contributes to tumor immune escape by modulating the immunosuppressive microenvironment, which was consistent with previous studies [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…Recent study indicated that 11-genes ferroptosis-related signature accurately predicts clinical prognosis in patients with CCRCC. 23 Intriguingly, these 4-genes ferroptosis-related signatures are specific for PRCC patients compared with the discovered ferroptosis-related signature in CCRCC, 23 , 24 which is benefit to develop specific clinical drugs and diagnostic strategies for PRCC patients only.…”
Section: Discussionmentioning
confidence: 96%